The Role of Extracellular Vesicles in β-Cell Function and Viability: A Scoping Review - Stephanie Chidester; Stephanie Chidester; Alicia A. Livinski; Anne F. Fish; Paule V. Joseph (Frontiers in Endocrinology, 2020)
Extracellular vesicles (EVs) released by cells throughout the body have been implicated in diabetes pathogenesis. Understanding the role of EVs in regulation of β-cell function and viability may provide insights into diabetes etiology and may lead to the development of more effective screening and diagnostic tools to detect diabetes earlier and prevent disease progression. This review was conducted to determine what is known from the literature about the effect of EV crosstalk on pancreatic β-cell function and viability in the pathogenesis of diabetes mellitus, to perform a gap analysis for future research directions, and to discuss implications of available evidence for diabetes care. The literature search yielded 380 studies from which 31 studies were determined to meet eligibility criteria. The majority of studies had the disease context of autoimmunity in T1DM. The most commonly studied EV crosstalk dynamics involved localized EV-mediated communication between β-cells and other islet cells, or between β-cells and immune cells. Other organs and tissues secreting EVs that affect β-cells include skeletal muscle, hepatocytes, adipocytes, immune cells, bone marrow, vascular endothelium, and mesenchymal stem cells. Characterization of EV cargo molecules with regulatory effects in β-cells was conducted in 24 studies, with primary focus on microRNA cargo. Gaps identified included scarcity of evidence for the effect on β-cell function and viability of EVs from major metabolic organs/tissues such as muscle, liver, and adipose depots. Future research should address these gaps as well as characterize a broader range of EV cargo molecules and their activity in β-cells.